PENDAMPINGAN MANAJEMEN PENGOLAHAN LIMBAH TERNAK KAMBING DI DESA TELUK SANTONG - Sukarne Sukarne; Yusuf Akhyar Sutaryono; Harjono Harjono; Syalsa Bella Fitriana (Jurnal Abdi Insani, 2026)
The assistance program for processing livestock waste into organic fertilizer was carried out in Teluk Santong Village, Plampang District, Sumbawa Regency, with the aim of enhancing the community’s knowledge and skills in managing livestock waste using simple technology. Livestock waste consists of manure (feces), urine, and feed residues. When properly processed, it can be utilized as organic fertilizer, which plays a role in improving soil and plant fertility while also having the potential to increase farmers’ income. The training on organic fertilizer production was carried out in two stages. The first stage comprised the delivery of materials through lectures and discussions, complemented by the distribution of brochures as a guide for participants to understand the procedures and techniques for producing organic fertilizer. The second stage consisted of hands-on practice to ensure that farmers could carry out the production process accurately and correctly. This training had a positive impact by enhancing the skills of livestock farmers in processing livestock waste into organic fertilizer. Furthermore, the organic fertilizer produced can be used for crops and helps reduce the dependence on increasingly expensive inorganic fertilizers. Organic fertilizer also contributes to improving soil conditions physically, chemically, and biologically—thereby maintaining soil fertility in Teluk Santong Village.